Nanaomycin K inhibited epithelial mesenchymal transition and tumor growth in bladder cancer cells in vitro and in vivo - Koichi Kitagawa (Nature Portfolio, 2021)
Abstract Nanaomycin K, derived from Streptomyces rosa subsp. notoensis OS-3966T, has been discovered to have inhibitory bioactivity on epithelial–mesenchymal transition (EMT), an important mechanism of cancer cell invasion and migration. In this study, we examined the anti-EMT and anti-tumor effect of nanaomycin K in bladder cancer, where EMT has important roles in progression. We treated two bladder cancer lines, non-muscle-invasive KK47 and muscle-invasive T24, with nanaomycin K to determine the effects on cell proliferation, apoptosis and expression of EMT markers in vitro. Wound-healing assays were performed to assess cell invasion and migration. We conducted an in vivo xenograft study in which mice were inoculated with bladder cancer cells and treated with intratumoral administration of nanaomycin K to investigate its anti-tumor and EMT inhibition effects. As the results, nanaomycin K (50 µg/mL) significantly inhibited cell proliferation in KK47 (p < 0.01) and T24 (p < 0.01) in the presence of TGF-β, which is an EMT-inducer. Nanaomycin K (50 µg/mL) also significantly inhibited cell migration in KK47 (p < 0.01) and T24 (p < 0.01), and induced apoptosis in both cell lines in the presence of TGF-β (p < 0.01). Nanaomycin K increased the expression of E-cadherin and inhibited the expression of N-cadherin and vimentin in both cell lines. Nanaomycin K also decreased expression of Snail, Slug, phospho-p38 and phospho-SAPK/JNK especially in T24. Intratumoral administration of nanaomycin K significantly inhibited tumor growth in both KK47 and T24 cells at high dose (1.0 mg/body) (p = 0.009 and p = 0.003, respectively) with no obvious adverse events. In addition, nanaomycin K reversed EMT and significantly inhibited the expression of Ki-67 especially in T24. In conclusion, we demonstrated that nanaomycin K had significant anti-EMT and anti-tumor effects in bladder cancer cells, suggesting that nanaomycin K may be a therapeutic candidate for bladder cancer treatment.